Stratifying Risk for Sudden Cardiac Death - Buckley, Rita (MD Conference Express, 2011)
A major challenge for the medical community is predicting who is at risk of sudden cardiac death (SCD). In the majority of patients, death is the first symptom of heart disease, making early risk stratification critical. This article discusses emerging strategies for risk stratification for SCD.